Pengaruh Keputusan Investasi, Struktur Modal, Kebijakan Deviden, dan Tingkat Profitabilitas terhadap Nilai Perusahaan - Nainggolan, Nurlina; Giawa, Baharudin; Sitorus, Jessy Safitri; Sanjaya, Ni Made Wulan Sari (Gorontalo Accounting Journal, 2023)
The main objective of this study is to prove the effect of investment decisions, capital structure, dividend policy and profitability level on firm value in non-cyclical consumer sector manufacturing companies on the Indonesia Stock Exchange for the 2019-2021 period by conducting partial and simultaneous analysis tests. The research method used is a quantitative approach with statistical data using multiple linear analysis with data processed with SPSS software version 25. This study uses purposive sampling technique in determining the criteria for determining the sample, so that 29 research samples are obtained with a total research sample of 87 companies. The coefficient of determination test results show that 48 8% of firm value is influenced by independent variables while the remaining 51.2% is influenced by variables outside the research path. The simultaneous test results prove that investment decision variables, capital structure, dividend policy and profitability simultaneously affect firm value. The test results of investment decision variables and dividend policy partially have no influence on firm value, but capital structure variables and profitability partially have a significant influence on firm value.